The Implementation of Islamic Inheritance Law in the Distribution of Inheritance in Indonesia - Hikmatullah Hikmatullah; Hafidz Amrullah; Meli Munjiah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of Islamic inheritance law in the distribution of inheritance in Indonesia. Islamic inheritance law is a fundamental component of Islamic jurisprudence that regulates the transfer of ownership rights from a deceased person to rightful heirs based on the Qur’an, Hadith, and classical fiqh principles. In practice, the implementation of Islamic inheritance law in Indonesia faces various challenges, including the influence of customary law, limited public understanding of faraidh, and family-based agreements that often disregard Islamic legal provisions. This study aims to analyze the implementation of Islamic inheritance law in Indonesia and identify the factors influencing its application within society. A qualitative method with a normative juridical approach was employed through library research using books, academic journals, statutory regulations, and other relevant scholarly sources. The findings indicate that the implementation of Islamic inheritance law in Indonesia is supported by the Compilation of Islamic Law (KHI) and the Religious Court system. However, its application remains suboptimal due to social, cultural, and educational factors affecting legal compliance. Strengthening legal education and increasing public awareness are essential to ensure that inheritance distribution aligns with Islamic legal principles and promotes justice within Muslim communities.